Effect of inoculum ratio for anaerobic digestion of hydrolyzed palm oil mill effluent for biogas production - Fazil, Nurul Alia; Alam, Md. Zahangir; Mansor, Mariatul Fadzillah; Azmi, Azlin Suhaida (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Production of biogas from various organic wastes has been a topic for wastes management and utilization. However, most research focuses more on raw or untreated organic waste, particularly POME than that on hydrolyzed POME. An appropriate ratio of inoculum to include in an anaerobic digester for producing biogas with hydrolyzed POME which has yet to be explored. This study aims to observe the effect of varying inoculum content in an anaerobic digester towards biogas production. Anaerobic sludge as inoculum was added to hydrolyzed and raw POME in ratio 10 to 50% v/v. Produced biogas was collected using liquid replacement method (LRM) and the volume was recorded daily for a duration of 10 days. The HRT was kept constant at 20 days. At 10% inoculum content, within the stable period, the biogas production was within the range of 55 ml to 80 ml daily which was significantly higher than the others with 70 – 77% volume difference. The total volume of biogas produced for 10% inoculum when compared to the same inoculum concentration with raw POME have significant 81.52% higher biogas production. Biogas production was notably better with hydrolyzed POME. Less inoculum utilization for higher biogas production was also obtained with better COD removal.